REVIEW OF THE ELIGIBILITY OF CHILDREN’S BOOKS TO THE CONGURITY OF THE SOCIAL STUDIES CURRICULA (K1-K3) - Şükran UÇUŞ; İbrahim GAFA and İrem DEMİRBAŞ and Zeki YILDIZ and Kadir SÖNMEZ (International Journal of Eurasia Social Sciences, 2017)
The purpose of the current study aimed at investigating children’s books, regarding objectives, units, values, skills congruity to social studies (K1-K3) curriculum. The study group is comprised of 300 books for children appealing to between age 6-9. Books were chosen on the basis of elementary school teachers’ opinions and the instructors’ opinion as for the field of the expert about children’s literature, best sale books in most well-known bookstores to compile a list. The method of current study is the descriptive model in a qualitative strand. The data was analyzed with document analysis, and it supported with quotes from books. Besides, frequencies and percentages were used for the analysis of data. To actualize document analysis in a common and objective framework, researchers developed a “Book Evaluation Form” as a book checklist for the curriculum. “Observation” and “Communication” are most common skills, “The love of Nature” and “Helping Each Other” are most common values, “Nature and Environment” unit and its objectives are mostly observed in the books regarding social studies curriculum. When it comes to rarely seen skill, value and units-objectives, using information technologies, awareness of national and cultural values, personal care, time management for skills; esthetic, patriotism, being scientific for values; “Nature and Environment” for grade 1st and grade 2nd’s units and their objectives, “Healthy Life” for grade 3rd were seldom observed in the target children’s books related to social studies (K1-K3).